2019
DOI: 10.1101/631895
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tropomyosin 1 genetically constrains in vitro hematopoiesis

Abstract: Identifying causal variants and genes from human genetics studies of hematopoietic traits are important to enumerate basic regulatory mechanisms underlying these traits, and could ultimately augment translational efforts to generate platelets and/or red blood cells in vitro. To identify putative causal genes from these data, we performed computational modelling using available genome-wide association data sets for platelet traits. Our model identified a joint collection of genomic features enriched at establis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…With interest in improving strategies to expand megakaryocyte and platelet production in vitro, he followed a human genetic approach to identify polymorphisms in TPM1 that lead to altered platelet traits. Using a primitive hematopoiesis system, wherein human iPSCs could be differentiated into primitive streak to the mesoderm stage, he interrogated the effect of loss of TPM1 compared with wild-type cultures (Thom et al, 2019(Thom et al, , 2020. The mesodermal cells normally acquire an endothelial fate, and the hemogenic population within this endothelium specifically undergo EMT to produce HPCs.…”
Section: Stem Cell Reportsmentioning
confidence: 99%
“…With interest in improving strategies to expand megakaryocyte and platelet production in vitro, he followed a human genetic approach to identify polymorphisms in TPM1 that lead to altered platelet traits. Using a primitive hematopoiesis system, wherein human iPSCs could be differentiated into primitive streak to the mesoderm stage, he interrogated the effect of loss of TPM1 compared with wild-type cultures (Thom et al, 2019(Thom et al, , 2020. The mesodermal cells normally acquire an endothelial fate, and the hemogenic population within this endothelium specifically undergo EMT to produce HPCs.…”
Section: Stem Cell Reportsmentioning
confidence: 99%
“…The refinement of iPSC systems to produce definitive-like hematopoiesis models [20,21] and increase in vitro cell production [8,62], will be essential for improving mechanistic studies, small molecule screening, and gene editing approaches. These models may also better support translational research goals in blood bank screening and cellular therapeutics [22].…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…This commentary has used selected vignettes to show how human iPSC model systems can be used to study mechanisms by which blood cells contribute to hematopoietic and nonhematopoietic disorders, and guide platform development for therapeutic approaches. The refinement of iPSC systems to produce definitive-like hematopoiesis models [23,24] and increase in vitro cell production [8,65], will be essential for improving mechanistic studies, small molecule screening, and gene editing approaches. These models may also better support translational research goals in blood bank screening and cellular therapeutics [25].…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Hematopoiesis is one of the best characterized developmental systems, given relatively accessible patient samples, and excellent cell and animal models [2,3]. Population studies have identified thousands of genomic loci that affect human blood traits [4], leading to translationally relevant developmental insights (e.g., [5][6][7][8][9][10]). Mechanistic studies using cells derived from clinically affected patients also offer increasingly powerful approaches to discover genetic factors that regulate hematopoiesis, and to identify novel treatment strategies.…”
Section: Introductionmentioning
confidence: 99%